The Mediating Role of Work Motivation in the Effects of Transformational Leadership, Reward System, and Work-Life Balance on Generation Z Employee Performance in Surabaya, Indonesia - Shafa Tasya Salsabila; Tommy Christian Efrata (UNIVED Press, 2026)
This study analyzes the effect of Transformational Leadership, Reward System, and Work-Life Balance on Employee Performance with Work Motivation as a mediating variable among Generation Z employees in Surabaya. Using a quantitative approach with cross-sectional design, data were collected from 200 respondents through Likert scale questionnaires and analyzed using SEM-PLS. Results showed that all three variables positively and significantly affect Work Motivation and Employee Performance, both directly and indirectly. Work Motivation acts as a partial mediator, explaining 62% of variance in employee performance. The structural model demonstrated substantial predictive power with R² of 62.2% for work motivation and 62.0% for employee performance. This study strengthens Self-Determination Theory in Indonesia's emerging market context and provides practical guidance for HR practitioners in designing transformational leadership strategies, adaptive reward systems, and work-life balance policies for Generation Z.